Understanding deviant teachings and its features among muslim youths: a case study of UNIKL students - Sakinah Munarwarrah, Hashim; Mohamad Lukman Al Hakim, Md. Noor; Muhammad Zamri, Abdul Ghani (Jurnal Hal Ehwal Islam Dan Warisan Selangor, 2019)
This paper presents the understanding of deviant teachings and its features among UniKL students and their opinions towards this issue. This paper will be focused on one of branch of UniKL institutions which is British Malaysian Institute at Gombak. 5 features characteristic of deviant teachings stated while focusing on two of the famous deviant teachings in Malaysia; Ayah Pin and Tuhan Harun. A questionnaire distributed asking understanding of student towards deviant teachings and its feature. Results shown that students are well aware on this issue, however, it is important for teachers to prioritize this matter and ensure that all students are aware and understand the concept of deviant teaching in order to protect their faith from anything that deviates from the true teachings of Islam.